Biostratigraphically significant palynofloras from the Paleocene–Eocene boundary of the USA. (2nd January 2023) - Korasidis, Vera A.; Wing, Scott L.; Harrington, Guy J.; Demchuk, Thomas; Gravendyck, Julia; Jardine, Phillip E.; Willard, Debra
Abstract: Pollen and spores were recovered from the Paleocene Fort Union Formation and Paleocene–Eocene Willwood Formation of the Bighorn Basin (BHB), northwestern Wyoming, USA. In many local stratigraphic sections in the BHB, the base of the Eocene has been identified by the characteristic negative carbon isotope excursion (CIE) that marks the beginning of the Paleocene–Eocene Thermal Maximum (PETM). The palynotaxa from outcrop samples were examined using light microscopy (LM) and scanning electron microscopy (SEM). Seven new species are formally described ( Tricolpites vegrandis, Rousea spatium, Striatricolporites astutus, Striatopollis calidarius, Friedrichipollis geminus, Retistephanocolporites modicrassus and Retistephanocolporites pergrandis ). The temporal and geographic distributions of many of these palynotaxa suggest that hotter and more seasonally dry climates facilitated their northward range shifts during the PETM from the tropics or subtropics of the USA. For the temperate palynotaxa, the hotter and seasonally dry conditions resulted in local extirpation. A re-evaluation of the palynostratigraphic schemes established for the Paleocene–Eocene boundary confirms that the first appearance of Platycarya platycaryoides denotes the Paleocene–Eocene boundary in the Rocky Mountains region. A new Striatopollis calidarius Subzone, associated with early Wasatchian (Wa) Wa-0 and Wa-R faunas, is also recognized for CIE body localities in the BHB.